2004
DOI: 10.1089/10430340460732490
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Intramuscular Injection of a Recombinant Adeno-Associated Virus Alpha 1-Antitrypsin (rAAV2-CB-hAAT) Gene Vector to AAT-Deficient Adults

Abstract: A recombinant virus vector constructed from adeno-associated virus (AAV) that has been altered to carry the human alpha1-antitrypsin (hAAT) gene expressed from a hybrid chicken beta-actin promoter with a cytomegalovirus enhancer has been developed. The construct has been shown to initiate the production of hAAT in animal models closely matching the proposed human trial. The proposed clinical trial is an open-label, phase I study administering recombinant adeno-associated virus alpha1-antitrypsin (rAAV2-CB-hAAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…This delivery system can be achieved by using AAV vectors. Recombinant AAV vectors have been used safely in clinical trials for a number of ocular diseases such as Leber congenital amaurosis 2325 and nonocular diseases that include hemophilia B, 26,27 cystic fibrosis, 28 α 1 -antitrypsin deficiency, 29 Parkinson disease, 30 Batten disease, 31 and muscular dystrophy. 32 The RGC layer exclusively affected in LHON can be targeted by optimizing the vector serotype, AAV2, and by choosing the route of vector administration, intravitreal injection, as we did here.…”
Section: Discussionmentioning
confidence: 99%
“…This delivery system can be achieved by using AAV vectors. Recombinant AAV vectors have been used safely in clinical trials for a number of ocular diseases such as Leber congenital amaurosis 2325 and nonocular diseases that include hemophilia B, 26,27 cystic fibrosis, 28 α 1 -antitrypsin deficiency, 29 Parkinson disease, 30 Batten disease, 31 and muscular dystrophy. 32 The RGC layer exclusively affected in LHON can be targeted by optimizing the vector serotype, AAV2, and by choosing the route of vector administration, intravitreal injection, as we did here.…”
Section: Discussionmentioning
confidence: 99%
“…If the date of the start of the trial was not available in clinicaltrials.gov website, the date of publication of the results is mentioned. The list of trials announced for 2017 is indicative and does not pretend to be exhaustiveYear (start of trial)Viral vectorDiseaseProductTherapeuticSponsorRouteDoseNumber of treated patientsStatusReference Clinicaltrial.gov identifier1992MoMLV Retrovirus 5Homozygous familial hypercholesterolaemiaNALDL receptor geneUniversity of Michigan Ann ArbourIntraportal (Ex vivo approach)1 to 3.3 × 10e9 hepatocytes5TerminatedGrossman et al 1994 Grossman et al 1995 Raper et al 1996 NCT000048091998Adenovirus 5Ornithine transcarbamylase deficiencyNAOTC geneUniversity of PennsylvaniaIntrahepatic2 × 10e9 to 6 × 10e11vg/kg18TerminatedRaper et al 2003 NCT000044981999AAV2Haemophilia BNAFactor IX geneNAIntramuscular2 × 10e11 to 1.8 × 10e12vg/kg8TerminatedKay et al 2000 Manno et al 2003 NA2003MoMLV RetrovirusHaemophilia ANAFVIII geneChironIntravenous2.8 × 10e7 to 4.4 × 10e8vg/kg13TerminatedPowell et al 2003 NA2004HD-AdenovirusHaemophilia ANAFVIII geneGenStarIntravenous4.3 × 10e10vg/kg1TerminatedChuah et al 2004 NA2004AAV2α1-antitrypsinNAhAAtUniversity MassachussetsIntramuscular2.1 × 10e12 to 6.9 × 10e13vg12TerminatedFlotte et al 2004 Brantly et al 2006 NCT003774162004AAV2Haemophilia BNAFactor IX geneAvigenIntrahepatic8 × 10e10 to 2 × 10e...…”
Section: Clinical Successes Of Liver-directed Aav-mediated Gene Therapymentioning
confidence: 99%
“…A first trial based on an AAV2 capsid showed an acceptable safety profile with mild local reactions at the site of intramuscular injection (redness, tenderness, bruising) and a seroconversion against AAV2. Unfortunately, only one out of 12 patients demonstrated a minimal increase of plasma M α1-antitrypsin at 82 nM (Flotte et al 2004; Brantly et al 2006). Two other trials (phase I then phase II) were conducted with a vector based on AAV1 capsid known for its better muscle transduction compared to AAV2 (Flotte et al 2011).…”
Section: Considerations For Paediatric Applicationmentioning
confidence: 99%
“…They are the focus of several phase 1/2 clinical trials involving a variety of different genetic disorders including hemophilia B, lysosomal storage disorders, inherited retinal degeneration, α-1 antitrypsin, and lipoprotein lipase deficiency. 1318 In addition to their excellent safety profile, the most attractive attribute of these vectors is their ability to mediate persistent therapeutic transgene expression after a single administration of vector in a variety of animal models. 7,8,1922 Emerging results from clinical trials suggest that long-term persistent expression of a transgene is indeed achievable in humans.…”
Section: Introductionmentioning
confidence: 99%